Positive electrode for secondary battery and secondary battery including the same

By adopting a double-layer coating method in the secondary battery positive electrode, using the sacrificial positive electrode material and the high-energy density positive electrode material, the problems of uneven adhesive distribution and limited single-layer electrode structure are solved, and better battery performance and high energy density are achieved.

JP7670814B2Active Publication Date: 2025-04-30LG ENERGY SOLUTION LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2023518308
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-10-14
Filing Date
2021-10-14
Publication Date
2025-04-30
Estimated Expiration
2041-10-14

AI Technical Summary

Technical Problem

In the existing secondary battery's positive electrode active layer, the adhesive distribution is uneven, resulting in a degradation of battery performance and the single-layer electrode structure limits performance improvement.

Method used

The positive electrode is manufactured by a double-layer coating method. The lower layer contains a sacrificial positive electrode material and a high-energy density positive electrode material. The upper layer contains a conductive material and an adhesive to ensure uniform distribution of the adhesive.

Benefits of technology

The bonding force of the electrode is improved through uniformly distributed adhesive, the electrochemical performance of the battery is improved, and the improvement of battery performance is maximized through the combination of materials at different levels.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007670814000002
    Figure 0007670814000002
  • Figure 0007670814000003
    Figure 0007670814000003
  • Figure 0007670814000004
    Figure 0007670814000004
Patent Text Reader

Abstract

When manufacturing a cathode of the same thickness, the present invention employs a double-layer coating method to achieve uniform binder distribution across the thickness of the electrode active material layer, and improves adhesion by allowing the binder resin in the lower layer of the cathode active material layer to remain in the lower layer. Furthermore, by differentiating the compositions of the cathode materials in the upper and lower layers of the cathode and adding a sacrificial cathode material only to the lower layer, the electrochemical characteristics of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode for a secondary battery. The present invention also relates to a secondary battery comprising said positive electrode.

[0002] This application claims priority to Korean Patent Application No. 10-2020-0132967 filed on October 14, 2020, Korean Patent Application No. 10-2020-0186566 filed on December 29, 2020, and Korean Patent Application No. 10-2021-0136984 filed on October 14, 2021, and the contents disclosed in the specification and drawings of such applications are incorporated into this application in their entirety. [Background technology]

[0003] Secondary batteries such as lithium-ion secondary batteries are being used in a variety of fields, from power sources for portable electronic devices such as notebook personal computers (PCs), mobile phones, digital cameras, and camcorders to electric vehicles thanks to the development of high-output, high-energy density batteries.

[0004] In order to improve the energy density of such secondary batteries, improve the high-rate characteristics, and develop high-capacity batteries, a technology has been proposed in which a Ni-rich lithium composite oxide material is used for the positive electrode and a silicon-based (silicon and / or silicon oxide) material is used for the negative electrode. In addition, when the Ni-rich lithium composite oxide is used as the positive electrode material, LNO (lithium nickel oxide, e.g., Li2NiO2), which has a high irreversible capacity, is used as a sacrificial positive electrode material, but such an LNO sacrificial positive electrode material has the disadvantage that the cost of LNO is high and the manufacturing cost increases. In addition, a sacrificial positive electrode material having a higher charge capacity and irreversible capacity than LNO is required.

[0005] Meanwhile, a secondary battery electrode is generally formed by coating an electrode current collector with an electrode slurry once, and in this case, the binder contained on the electrode slurry is not uniformly dispersed in the coated electrode active material layer, and instead floats to the surface of the electrode active material layer. In this case, the binder increases the resistance of the battery, causing a problem of reduced battery performance. This problem becomes more severe as the load of the electrode active material increases. In addition, while the battery performance can be further improved by unevenly distributing the electrode material in a specific part of the electrode, such as the upper or lower layer of the electrode, the conventional single-layer electrode has been limited in its ability to achieve such improved performance.

[0006] Therefore, there is a need to develop a high-capacity secondary battery with an increased capacity of the electrode active material, and an electrode having multiple electrode active material layers in which an appropriate electrode material is disposed in each layer in order to maximize the performance improvement effect of the secondary battery. Summary of the Invention [Problem to be solved by the invention]

[0007] The present invention aims to provide a positive electrode for a secondary battery having a positive electrode active material layer with a uniform binder distribution in the thickness direction. Another aim of the present invention is to provide a positive electrode for a secondary battery having a multi-layer positive electrode active material layer in which the composition of the positive electrode material in the upper layer and the lower layer of the positive electrode is different, and an appropriate positive electrode material is disposed in each layer.

[0008] Another object of the present invention is to provide a battery including a sacrificial cathode material for compensating for the irreversible capacity and reducing gas generation that occurs when a Ni-rich lithium composite oxide material is used as a cathode active material, and in particular to provide a cathode for a secondary battery in which the sacrificial cathode material is disposed in the lower layer of the cathode to prevent deterioration of the sacrificial cathode material due to contact with air.

[0009] Finally, the present invention aims to provide a battery using single-walled carbon nanotubes (SWCNTs) as a conductive material to ensure electrical conductivity of a silicon-based negative electrode.

[0010] The objects and advantages of the present invention can be realized by the means or methods recited in the claims and combinations thereof. [Means for solving the problem]

[0011] According to a first aspect of the present invention, a positive electrode for a secondary battery includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, the positive electrode active material layer including a lower layer disposed on a surface of the current collector and an upper layer disposed on an upper surface of the lower layer, the upper layer including a first positive electrode active material, a conductive material, and a binder resin, the lower layer including a second positive electrode active material, a sacrificial positive electrode material, a conductive material, and a binder resin, and the first and second positive electrode active materials each independently include at least one compound represented by Chemical Formula 1 below:

[0012] [Chemical formula 1] LiNi 1-x M x O2

[0013] In the above Chemical Formula 1, M includes at least one of Mn, Co, Al, Cu, Fe, Mg, B, and Ga, and x is 0 to 0.5.

[0014] According to a second aspect of the present invention, in the first aspect, the sacrificial cathode material in the lower layer includes at least one of Li6CoO4 and a compound represented by the following Chemical Formula 2:

[0015] [Chemical formula 2] Li6Co 1-x Zinc x O4

[0016] In the above Chemical Formula 2, x is 0 or more and 1 or less.

[0017] According to a third aspect of the present invention, in the first or second aspect, the sacrificial positive electrode material is Li6CoO4, Li6Co 0.7 Zinc 0.3 Includes one or more selected from O4.

[0018] According to a fourth aspect of the present invention, in any one of the first to third aspects, the sacrificial positive electrode material is contained in a range of 1 wt % to 20 wt % with respect to 100 wt % of the lower layer.

[0019] According to a fifth aspect of the present invention, in any one of the first to fourth aspects, the sacrificial positive electrode material is contained in an amount of 10 wt % or less relative to 100 wt % of the entire positive electrode active material layer.

[0020] According to a sixth aspect of the present invention, in any one of the first to fifth aspects, in the chemical formula 1, x is 0 or more and 0.15 or less.

[0021] According to a seventh aspect of the present invention, in any one of the first to sixth aspects, in the Chemical Formula 1, M includes two or more of Co, Al, and Mn.

[0022] According to an eighth aspect of the present invention, in any one of the first to seventh aspects, in the chemical formula 1, the positive electrode active material is LiNi 1-x (Co, Mn, Al) x O2, and the Al is contained in an atomic ratio of 0.001 to 0.02 relative to Ni.

[0023] According to a ninth aspect of the present invention, there is provided a lithium ion secondary battery comprising a positive electrode, a negative electrode, an insulating separator interposed between the positive electrode and the negative electrode, and an electrolyte solution; The positive electrode is a positive electrode described in any one of sides 1 to 8, The negative electrode contains a silicon-based compound as a negative electrode active material, The conductive material includes a linear conductive material.

[0024] According to a tenth aspect of the present invention, in the ninth aspect, the silicon-based compound includes one or more compounds represented by the following Chemical Formula 3:

[0025] [Chemical formula 3] SiO x

[0026] In the above Chemical Formula 3, x is 0 or more and less than 2.

[0027] According to an eleventh aspect of the present invention, in the tenth aspect, the x is equal to or greater than 0.5 and equal to or less than 1.5.

[0028] According to a twelfth aspect of the present invention, in either the ninth or eleventh aspect, the linear conductive material includes at least one selected from SWCNT, MWCNT (multi-walled CNT), and graphene.

[0029] According to a thirteenth aspect of the present invention, in either the ninth or twelfth aspect, the linear conductive material includes SWCNTs. Effect of the Invention

[0030] The present invention provides the following advantages.

[0031] 1) When manufacturing a positive electrode of the same thickness, the present invention applies a double-layer coating method to uniformly distribute the binder in the thickness direction of the electrode active material layer, and the binder resin in the lower layer of the positive active material can be maintained in the lower layer, thereby improving the binding strength.

[0032] 2) By making the composition of the positive electrode material in the upper and lower layers of the positive electrode different, and in particular by adding a sacrificial positive electrode material only to the lower layer, the electrochemical characteristics of the battery can be improved.

[0033] 3) In addition, the secondary battery of the present invention uses lithium cobalt oxide, in which part of the cobalt in the positive electrode is replaced with Zn, as a sacrificial positive electrode material to complement the irreversible capacity of the battery, while the lithium cobalt oxide acts as a gas eliminator to reduce the amount of gas generated inside the battery.

[0034] 4) The secondary battery according to the present invention contains a Ni-rich lithium composite oxide as the positive electrode active material and a silicon oxide as the negative electrode active material, and therefore it is possible to manufacture a high-capacity battery.

[0035] 5) Finally, the secondary battery according to the present invention uses SWCNTs as the negative electrode conductive material, making it possible to ensure that the electrical conductivity of the negative electrode containing silicon oxide is sufficient for battery operation.

[0036] The following drawings attached to this specification are for illustrating preferred embodiments of the present invention, and serve to further understand the technical idea of ​​the present invention together with the detailed description of the invention, so the present invention should not be interpreted as being limited to only the matters described in the drawings. In addition, the shape, size, scale, ratio, etc. of the elements in the drawings attached to this specification may be exaggerated in order to emphasize a clearer description. [Brief description of the drawings]

[0037] [Figure 1] 3 shows the weekly charging capacity of the battery according to Example 1. [Diagram 2] 3 shows the weekly discharge capacity of the battery according to Example 1. [Diagram 3] 4 shows the weekly charging capacity of the battery according to Comparative Example 1. [Figure 4] 4 shows the weekly discharge capacity of the battery according to Comparative Example 1. [Diagram 5] The time course of the various by-products produced during the decomposition of Li6CoO4 after exposure to air is shown. [Figure 6] The time course of the various by-products produced during the decomposition of Li6CoO4 after exposure to air is shown. [Figure 7]2 shows the capacity retention rates due to cycles in Example 2-1, Comparative Example 2, and Comparative Example 3. [Figure 8] 1 shows the capacity retention rate due to cycles in Example 2-1 and Example 2-2. [Figure 9] 1 shows the capacity retention rate depending on the C rate and cycles in Example 3, Comparative Example 4, and Comparative Example 5. [Figure 10] 1 shows the capacity retention rate depending on the C rate and cycles in Example 3, Comparative Example 4, and Comparative Example 5. [Figure 11] 1 shows the capacity retention rate depending on the C rate and cycles in Example 3, Comparative Example 4, and Comparative Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0038] Hereinafter, a preferred embodiment of the present invention will be described in detail with reference to the attached drawings. Prior to this, the terms and words used in this specification and claims should not be interpreted as being limited to their ordinary or dictionary meanings, but should be interpreted as being in accordance with the meaning and concept of the technical idea of ​​the present invention, in accordance with the principle that the inventor himself can appropriately define the concept of the term in order to best describe the invention. Therefore, it should be understood that the embodiment described in this specification and the configuration shown in the drawings are only one most preferred embodiment of the present invention, and do not represent the entire technical idea of ​​the present invention, and therefore there may be various equivalents and modifications that can be substituted for them at the time of this application.

[0039] In addition, throughout the specification, when a part "includes" a certain component, this does not mean excluding other components, but means that it may further include other components, unless specifically stated to the contrary.

[0040] The terms "about," "substantially," and the like, used throughout this specification, when given the meaning inherent in the manufacturing and material tolerances, are used to mean a numerical value or a approximation thereof, and are used to prevent unconscionable infringers from unfairly using disclosures in which precise or absolute numerical values ​​are recited to aid in the understanding of this application.

[0041] Throughout this specification, the phrase "A and / or B" means "A or B, or all of these."

[0042] Certain terminology is used in the following detailed description for convenience only and is not limiting. The words "right", "left", "top" and "bottom" designate directions in the drawings to which reference is made. The words "inward" and "outward" designate directions toward or away from the geometric center of the designated device, system and components thereof, respectively. "Front", "rear", "upper", "lower" and related words and phrases designate locations and orientations in the drawings to which reference is made and are not limiting. Such terms include the example words above, derivatives thereof and words of similar import.

[0043] The first aspect of the present invention relates to a positive electrode for a secondary battery, which is a device that converts chemical energy into electrical energy through an electrochemical reaction and can be charged and discharged, specific examples of which include lithium ion batteries, nickel-cadmium batteries, and nickel-hydrogen batteries.

[0044] In the present invention, the positive electrode includes a positive electrode current collector and a positive electrode active material layer formed on at least one surface of the current collector, and the positive electrode active material layer includes a positive electrode active material, a conductive material, and a binder resin.

[0045] In a specific embodiment of the present invention, the positive electrode active material layer has a multi-layer structure including a lower layer and an upper layer. The lower layer is disposed on a surface of a current collector and means a layer in contact with the current collector. The upper layer is disposed on a surface of the lower layer and means a layer facing a separator during the manufacture of a battery. In one embodiment of the present invention, one or more additional electrode active material layers may be further interposed between the upper layer and the lower layer.

[0046] The upper layer includes a positive electrode active material, a conductive material, and a binder resin. The lower layer includes a positive electrode active material, a sacrificial positive electrode material, a conductive material, and a binder resin. The upper layer preferably does not include a sacrificial positive electrode material. That is, in the positive electrode according to the present invention, the sacrificial positive electrode material is provided so as not to be exposed through a surface portion of the positive electrode active material layer. In one embodiment of the present invention, the additional electrode active material layer may or may not include a sacrificial positive electrode material. Preferably, the additional electrode active material layer does not include a sacrificial positive electrode material.

[0047] In a specific embodiment of the present invention, the positive electrode active material includes a Ni-rich lithium composite oxide represented by the following Chemical Formula 1:

[0048] [Chemical formula 1] LiNi 1-x M x O2

[0049] In the formula 1, M is at least one of Mn, Co, Al, Cu, Fe, Mg, B, and Ga. Preferably, M is at least two of Co, Al, and Mn. In the formula 1, x may have a value of 0 to 0.5, preferably 0 to 0.3, more preferably 0 to 0.15. In one embodiment of the present invention, M may include at least one of Co, Mn, and Al. In one specific embodiment of the present invention, the positive electrode active material is LiNi 1-x (Co, Mn, Al) x O 2 , where Al may be contained in an atomic ratio of 0.001 to 0.02 relative to Ni.

[0050] Preferably, the positive electrode active material layer contains 90 wt % or more of the Ni-rich lithium composite oxide of Formula 1 with respect to 100 wt % of the positive electrode active material.

[0051] In one embodiment of the present invention, the upper layer and the lower layer each independently contain 90 wt % or more of the Ni-rich lithium composite oxide of Formula 1, based on 100 wt % of the positive electrode active material.

[0052] If necessary, in addition to the Ni-rich lithium composite oxide of the above formula 1, lithium manganese composite oxides (LiMn2O4, LiMnO2, etc.), lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), and other layered compounds and compounds substituted with one or more transition metals; 1+x Mn 2-x Lithium manganese oxides such as LiMnO3, LiMn2O3, and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiV3O4, V2O5, and Cu2V2O7; and the chemical formula LiNi 1-x M x Lithium nickel oxide with Ni site represented by the chemical formula LiMnO2 (where M=Co, Mn, Al, Cu, Fe, Mg, B or Ga, and x=0.01 to 0.3); 2-x M x The lithium manganese composite oxide represented by Li2Mn3MO8 (wherein M is Co, Ni, Fe, Cr, Zn, or Ta, and x is 0.01 to 0.1) or Li2Mn3MO8 (wherein M is Fe, Co, Ni, Cu, or Zn); LiMn2O4 in which part of the Li in the chemical formula is replaced with an alkaline earth metal ion; a disulfide compound; or a mixture of two or more of Fe2(MoO4)3.

[0053] The binder resin may include a polyvinylidene fluoride (PVDF)-based polymer and / or an acrylic-based polymer. In one embodiment of the present invention, the PVDF-based polymer may include at least one of vinylidene fluoride and a copolymer of vinylidene fluoride and a monomer copolymerizable therewith; and a mixture thereof. In one embodiment of the present invention, the monomer may be, for example, a fluorinated monomer and / or a chlorine-based monomer. Non-limiting examples of the fluorinated monomer include vinyl fluoride; trifluoroethylene (TrFE); chlorofluoroethylene (CTFE); 1,2-difluoroethylene; tetrafluoroethylene (TFE); hexafluoropropylene (HFP); perfluoro(alkyl vinyl) ethers such as perfluoro(methyl vinyl) ether (PMVE), perfluoro(ethyl vinyl) ether (PEVE), and perfluoro(propyl vinyl) ether (PPVE); perfluoro(1,3-dioxole); and perfluoro(2,2-dimethyl-1,3-dioxole) (PDD), and may include at least one of these. In one embodiment of the present invention, the PVDF-based polymer may include at least one selected from polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyvinylidene fluoride-chlorofluoroethylene (PVDF-CTFE), polyvinylidene fluoride-tetrafluoroethylene (PVDF-TFE), and polyvinylidene fluoride-trifluoroethylene (PVDF-TrFE). For example, the PVDF-based polymer may include at least one selected from PVDF-HFP, PVDF-CTFE, and PVDF-TFE. Preferably, the PVDF-based polymer may include at least one selected from PVDF-HFP and PVDF-CTFE. In the present invention, the acrylic polymer may include, for example, a (meth)acrylic polymer.The (meth)acrylic polymer contains a (meth)acrylic acid ester as a monomer, and such monomer may include monomers such as butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, ethyl (meth)acrylate, methyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, n-oxyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, lauryl (meth)acrylate, and tetradecyl (meth)acrylate, and may contain one or more of these.

[0054] The conductive material may be, for example, any one selected from the group consisting of graphite, carbon black, carbon or metal fiber, metal powder, conductive whisker, conductive metal oxide, activated carbon, and polyphenylene derivatives, or a mixture of two or more of these conductive materials. More specifically, the conductive material may be any one selected from the group consisting of natural graphite, artificial graphite, super-p, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, denka black, aluminum powder, nickel powder, zinc oxide, potassium titanate, and titanium oxide, or a mixture of two or more of these conductive materials.

[0055] The sacrificial cathode material plays a role of easily providing lithium that can be used to meet the demand for lithium generated by an irreversible electrochemical reaction at the anode during an initial charging reaction. As described above, in order to manufacture a high-capacity secondary battery, a lithium composite metal oxide with a high Ni content (Ni-rich cathode active material) is used as a cathode active material and a Si material is used at the anode, but the addition of a sacrificial cathode material is required to easily provide lithium at the cathode due to the irreversible electrochemical reaction at the anode.

[0056] In one embodiment of the present invention, the sacrificial cathode material may include a lithium composite oxide containing cobalt in order to supplement the irreversible capacity of the Ni-rich cathode active material. In one embodiment of the present invention, the lithium composite oxide containing cobalt may include at least one of Li6CoO4 and a compound represented by the following Formula 2:

[0057] [Chemical formula 2] Li6Co 1-x Zinc x O4

[0058] In the formula 2, x may have a value of 0 to 1. Preferably, x is greater than 0. The sacrificial cathode material is, for example, Li6CoO4, Li6Co 0.7 Zinc 0.3 O4.

[0059] Meanwhile, the sacrificial cathode material easily reacts with moisture and carbon dioxide in the air to generate by-products such as Li6C, CoO, LiOH, Co(OH)2, and Li2CO3. Figures 5 and 6 show that when Li6CoO4 is left in the air for 1 hour to 7 days, various by-products are formed. The unit in Figure 5 is %, and the weight of each component is shown as a percentage of the total amount of by-products generated in each measurement. Figure 6 shows the FT-IR measurement results of the generated by-products. In Figure 6, bar (1) indicates Li6CoO4, bar (2) indicates Li2CO3, bar (3) indicates Co(OH)2, and bar (4) indicates CoO. These are the bars that are prominently shown in Figure 6, and detection results for each component have been confirmed from specific WLs. Therefore, in the present invention, in order to prevent the sacrificial cathode material from coming into contact with the air, it is arranged so that it is not included in the upper layer (or top layer) of the electrode active material layer and is unevenly distributed in the lower layer (or bottom layer) of the electrode active material layer.

[0060] In one embodiment of the present invention, the sacrificial positive electrode material may be included in a range of about 1 wt% to 20 wt% based on 100 wt% of the lower layer, and may be included in an amount of 10 wt% or less based on 100 wt% of the entire positive electrode active material layer.

[0061] In one embodiment of the present invention, the sacrificial positive electrode material Li6CoO4 has a particle size D50 larger than the particle size D50 of the positive electrode active material particles, and as a specific example, the particle size D50 of the sacrificial positive electrode material may be in the range of 10 μm to 25 μm.

[0062] The sacrificial positive electrode material plays a role of a sacrificial positive electrode material that complements the irreversible capacity of the secondary battery of the present invention, and at the same time, plays a role of a gas eliminator that reduces gas generation during battery operation. Thus, the secondary battery of the present invention can prevent capacity reduction and reduce the amount of gas generation by including the sacrificial positive electrode material.

[0063] The positive electrode active material and the binder resin in the lower and upper layers of the positive electrode active material layer may be independently contained in a weight ratio of 80:20 to 99:1.

[0064] Meanwhile, the conductive material may be included in the lower layer in an amount of 0.4 wt% to 1.5 wt% relative to 100 wt% of the lower layer, and in the upper layer in an amount of 0.4 wt% to 1.0 wt% relative to 100 wt% of the upper layer. In the case of the lower layer, the LiCoO4 contained as a sacrificial cathode material has a large particle size and low conductivity compared to the cathode active material, so the conductive material content in the lower layer needs to be higher than that in the upper layer.

[0065] Meanwhile, in one embodiment of the present invention, the thickness of the lower layer may be 40% to 60% of the total thickness of the positive electrode active material layer (100%).

[0066] The current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity, and may be, for example, stainless steel, copper, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, or the like.

[0067] The positive electrode according to the present invention can be produced, for example, by a method in which a lower layer is formed on one surface of a current collector, and an upper layer is formed on the surface of the lower layer.

[0068] The method for producing the positive electrode is not limited to a single method, as long as a positive electrode having the above-described structure is provided.

[0069] For example, a suitable solvent is first prepared, and a binder resin, a conductive material, a positive electrode active material, and a sacrificial positive electrode material are added to the solvent to prepare a slurry for the lower layer. The order in which the materials are added may be determined appropriately in consideration of dispersibility. Next, the slurry for the lower layer is applied to a surface of a current collector and dried. The lower layer may be selectively formed on both sides or one side of the current collector.

[0070] Next, an upper layer is formed on the surface of the lower layer prepared as described above.

[0071] In the case of the upper layer, a solvent is prepared, and a binder resin, a conductive material, a positive electrode active material, and a sacrificial positive electrode material are added to the solvent to prepare a slurry for the lower layer. The order of adding the materials may be appropriately determined in consideration of dispersibility. Then, the prepared slurry for the upper layer is applied to the surface of the lower layer and dried.

[0072] Non-limiting examples of the solvent include one or a mixture of two or more selected from the group consisting of water, acetone, tetrahydrofuran, methylene chloride, chloroform, dimethylformamide, N-methyl-2-pyrrolidone (NMP) and cyclohexane. Next, the slurry for the lower layer is applied to the surface of the current collector.

[0073] The coating method may be a coating method known in the art, such as dip coating, die coating, roll coating, comma coating, Mayer bar, die coating, reverse roll coating, gravure coating, or a mixture thereof. The drying method may be any of the usual drying methods, such as natural drying and air drying, without any particular limitation.

[0074] Meanwhile, in one embodiment of the present invention, after the lower layer slurry is applied and before drying, the upper layer slurry may be applied, and both the upper layer and the lower layer may be subjected to a drying process.

[0075] The present invention also provides a secondary battery including the positive electrode. The secondary battery includes a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, and the positive electrode has the structural features according to the present invention.

[0076] On the other hand, a second aspect of the present invention relates to an electrochemical device including the positive electrode and a secondary battery including the electrochemical device.

[0077] The secondary battery is a device that converts chemical energy into electrical energy through an electrochemical reaction and is capable of being charged and discharged. Specific examples of the secondary battery include a lithium ion battery, a nickel-cadmium battery, and a nickel-hydrogen battery. In the present invention, the secondary battery may be preferably a lithium ion secondary battery. Accordingly, the present specification will be described by taking a lithium ion secondary battery as an example. The lithium ion secondary battery includes a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode. Next, the lithium ion secondary battery will be described in detail for each component.

[0078] According to one aspect of the present invention, the negative electrode includes a negative electrode current collector and a negative electrode active material layer formed on at least one surface of the current collector, the negative electrode active material layer including a negative electrode active material, a conductive material, and a binder resin.

[0079] According to one aspect of the present invention, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on at least one surface of the negative electrode current collector. The negative electrode active material layer includes graphite and a silicon-based compound as negative electrode active materials, and the graphite and the silicon-based compound may be included in a weight ratio ranging from 70:30 to 99:1. In one embodiment of the present invention, the silicon-based compound may include silicon and / or silicon oxide. In one embodiment of the present invention, the silicon oxide may include one or more compounds represented by the following Chemical Formula 3:

[0080] [Chemical formula 3] SiO x

[0081] In Formula 3, 0≦x<2. In Formula 3, in the case of SiO2 (where x=2 in Formula 1), it is preferable that x is less than 2 because SiO2 does not react with lithium ions and cannot store lithium. Specifically, in terms of structural stability of the electrode active material, x may be 0.5≦x≦1.5.

[0082] Meanwhile, in one embodiment of the present invention, the silicon-based compound may further include a carbon coating layer that covers the entire or at least a part of the surface of the active material particles. The carbon coating layer may function as a protective layer that suppresses the volume expansion of the negative active material particles containing the silicon-based compound and prevents side reactions with the electrolyte. The carbon coating layer is included in the silicon-based compound in an amount of 0.1 wt % to 10 wt %, preferably 3 wt % to 7 wt %, and when the carbon coating layer is included in the silicon-based compound, it is preferable in that the carbon coating layer can control the volume expansion of the negative active material particles containing the silicon-based compound to an excellent level while preventing side reactions with the electrolyte.

[0083] Meanwhile, in one embodiment of the present invention, the negative electrode active material particles containing the silicon-based compound have a particle size D 50 The particle size D may be 3 μm to 10 μm, preferably 3 μm to 10 μm. 50If the specific surface area is less than 3 μm, the reaction area with the electrolyte increases due to the high specific surface area, which may increase the frequency of side reactions with the electrolyte during charging and discharging, thereby shortening the battery life.On the other hand, if the specific surface area exceeds 10 μm, the volume change due to the volume expansion / contraction of the active material particles during charging and discharging is large, which may cause cracks or breakage in the active material particles, resulting in deterioration and a decrease in battery performance.

[0084] Meanwhile, the graphite may include at least one selected from artificial graphite and natural graphite. The natural graphite may be unprocessed natural graphite such as flake graphite, flaky graphite, and earthy graphite, or spheroidized natural graphite. Spheroidal graphite and flaky graphite show almost perfect crystallinity, and earthy graphite has lower crystallinity. In consideration of the electrode capacity, spheroidal graphite and flaky graphite having high crystallinity may be used. For example, the spheroidized graphite may be used. In the case of the spheroidized natural graphite, the particle size may be 5 to 30 μm, preferably 10 to 25 μm.

[0085] The artificial graphite is generally prepared by a graphitization method in which raw materials such as coal tar, coal tar pitch, and petroleum-based medium oil are sintered at 2,500° C. or higher, and after the graphitization, the artificial graphite is used as a negative electrode active material through particle size adjustment such as pulverization and secondary particle formation.

[0086] In general, artificial graphite has crystals randomly distributed in the particles, and has a lower sphericity and a somewhat sharp shape compared to natural graphite. The artificial graphite may be in the form of powder, flakes, blocks, plates, or rods, and it is preferable that the orientation of the crystal grains is isotropic so that the migration distance of lithium ions is shortened to improve output characteristics. In consideration of this, the artificial graphite may be in the form of flakes and / or plates.

[0087] The artificial graphite used in one embodiment of the present invention may be commercially available mesophase carbon microbeads (MCMB), mesophase pitch-based carbon fiber (MPCF), artificial graphite graphitized in a block form, artificial graphite graphitized in a powder form, etc. The artificial graphite may have a particle size of 5 to 30 μm, preferably 10 to 25 μm.

[0088] The specific surface area of ​​the artificial graphite can be measured by the BET (Brunauer-Emmett-Teller) method. For example, it can be measured by the BET 6-point method using a porosimetry analyzer (Belsorp-II mini, Bell Japan) by nitrogen gas adsorption and flow. The specific surface area of ​​natural graphite described below can be measured by the same method.

[0089] The tap density of the artificial graphite is 0.7 g / cc to 1.1 g / cc, and preferably 0.8 g / cc to 1.05 g / cc. If the tap density is less than 0.7 g / cc, the contact area between particles is insufficient, resulting in a decrease in adhesion properties and a decrease in capacity per volume, while if the tap density is more than 1.1 g / cc, the tortuosity of the electrode and the wettability of the electrolyte are decreased, resulting in a decrease in output characteristics during charging and discharging, which is undesirable.

[0090] Here, the tap density is measured by putting 50 g of the precursor into a 100 cc tapping cylinder and tapping it 3000 times using a COPLEY JV-1000 measuring device or a SEISHIN (KYT-4000) measuring device. The tap density of natural graphite described below is measured in the same manner.

[0091] In addition, the artificial graphite may have an average particle diameter D50 of 8 μm to 30 μm, preferably 12 μm to 25 μm. If the average particle diameter D50 of the artificial graphite is less than 8 μm, the initial efficiency of the secondary battery may decrease due to an increase in specific surface area, and the battery performance may decrease. If the average particle diameter D50 exceeds 30 μm, the adhesive strength may decrease and the packing density may be low, resulting in a decrease in capacity.

[0092] The average particle size of the artificial graphite can be measured, for example, by using a laser diffraction method. The laser diffraction method can usually measure particle sizes from the submicron region to several mm, and can obtain results with high reproducibility and high resolution. The average particle size D50 of the artificial graphite can be defined as the particle size at 50% of the particle size distribution. The average particle size D50 of the artificial graphite can be measured, for example, by dispersing the artificial graphite in an ethanol / water solution, introducing it into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT3000), irradiating it with ultrasonic waves of about 28 kHz at an output of 60 W, and then calculating the average particle size D50 at 50% of the particle size distribution in the measuring device. The same method is also used to measure other particle sizes of the artificial graphite of the present invention.

[0093] In a specific embodiment of the present invention, the conductive material may be, for example, any one selected from the group consisting of graphite, carbon black, carbon nanotubes, carbon or metal fibers, metal powder, conductive whiskers, conductive metal oxides, activated carbon, and polyphenylene derivatives, or a mixture of two or more of these conductive materials. More specifically, the conductive material may be any one selected from the group consisting of natural graphite, artificial graphite, super-p, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, denka black, aluminum powder, nickel powder, zinc oxide, potassium titanate, and titanium oxide, or a mixture of two or more of these conductive materials.

[0094] In particular, in the present invention, the negative electrode conductive material preferably includes at least one linear conductive material having line or surface contact, such as carbon nanotubes, more preferably single-walled carbon nanotubes (SWCNT), multi-walled carbon nanotubes (MWCNT), and graphene, considering that the content of the silicon-based compound as the negative electrode active material is high. When a silicon-based compound is used as the negative electrode active material, the capacity of the electrode can be increased, but the volume change due to charging and discharging is large, Li consumption is large, and a thick SEI film is formed on the surface, which causes isolation due to the disconnection of contact between particles, and the electrochemical efficiency is low compared to carbon-based negative electrode materials such as graphite. Therefore, by including a linear conductive material such as SWCNT, the contact between particles of materials such as Si, which are easily isolated, can be increased, thereby improving the life characteristics. In one embodiment of the present invention, the linear conductive material may have a length of 0.5 μm to 100 μm. For example, the SWCNTs may have an average length of 2 μm to 100 μm, and the MWCNTs may have an average length of 0.5 μm to 30 μm, while the linear conductive material may have a cross-sectional diameter of 1 nm to 70 nm.

[0095] The current collector is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery. For example, stainless steel, copper, aluminum, nickel, titanium, baked carbon, or copper, aluminum, or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. may be used. The thickness of the current collector is not particularly limited, but may be a commonly used thickness of 3 to 500 μm.

[0096] The binder resin may be a polymer commonly used in electrodes in the art. Non-limiting examples of such binder resins include polyvinylidene fluoride-co-hexafluoropropylene, polyvinylidene fluoride-trichloroethylene, polymethylmethacrylate, polyethylhexyl acrylate, polybutylacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, ethylene-vinyl acetate copolymer, polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, and cellulose acetate propionate. Examples of suitable cellulose acetate copolymers include, but are not limited to, cyanoethyl acetatepropionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, and carboxyl methyl cellulose.

[0097] The separator is not particularly limited as long as it is used as a separator for a secondary battery. The separator may be any separator that has electrical insulation properties and provides an ion conduction path and is usable as a separator for an electrochemical device in the technical field without limitation. For example, a porous sheet including a polymer material such as a polymer film or a nonwoven fabric may be used as the separator. In one embodiment of the present invention, the separator may further include a heat-resistant coating layer including inorganic particles formed on a surface of the porous sheet.

[0098] The method for manufacturing the electrode assembly is not limited to a specific method. For example, when the positive electrode, the negative electrode, and the separator are prepared, the positive electrode / separator / negative electrode may be stacked in this order to prepare an electrode assembly, and the electrode assembly may be placed in a suitable case and an electrolyte may be injected to manufacture a battery.

[0099] In the present invention, the electrolyte is + B - A salt having the structure: + Li + , Na + , K + or a combination thereof, such as B - PF6 - , BF4 - , Cl - , Br - , I - , ClO4 - , AsF6 - , CH3CO2 - , CF3SO3 - , N(CF3SO2)2 - , C(CF2SO2)3 -Examples of the salts containing anions such as those listed above or ions consisting of a combination thereof are dissolved or dissociated in an organic solvent consisting of propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone (NMP), ethyl methyl carbonate (EMC), γ-butyrolactone, or a mixture thereof, but are not limited thereto.

[0100] The present invention also provides a battery module including a battery having the electrode assembly as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source. Specific examples of the device include, but are not limited to, a power tool powered by an electric motor, electric vehicles including electric vehicles (EV), hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV), and the like, electric two-wheeled vehicles including electric bicycles (E-bikes) and electric scooters (E-scooters), electric golf carts, and power storage systems.

[0101] Hereinafter, the present invention will be described in detail with reference to examples in order to specifically explain the present invention. However, the embodiments according to the present invention can be modified in various ways, and the scope of the present invention is not limited to the following examples. The examples of the present invention are provided to more completely explain the present invention to those having average knowledge in the art.

[0102] Example 1 (Double Layer Positive Electrode) (1) Preparation of the positive electrode Cathode active material (LiNi0 .89 Co 0.07 Mn 0.04 Al 0.01A slurry (solid content 70 wt%) for forming the lower positive electrode active material layer was prepared by adding the positive electrode active material (LiNiO2), binder (PVDF), conductive material (CNT bundle), and sacrificial positive electrode material (Li6CoO2) to NMP in a weight ratio of 96.65:1.34:0.84:1.17. This was applied to an aluminum thin film (thickness about 10 μm) and dried at 60 °C for 6 hours to form the lower layer of the electrode active material layer. Next, the positive electrode active material (LiNi 0.89 Co 0.01 Mn 0.1 O2), binder (PVDF) and conductive material (CNT bundles) were added to NMP in a weight ratio of 98.74:0.66:0.6 to prepare a slurry (solid content 70wt%) for forming the upper positive electrode active material layer. This was applied to the surface of the lower layer and dried at 60°C for 6 hours to form the upper layer of the electrode active material layer.

[0103] The thickness ratio of the upper electrode active material layer to the lower electrode active material layer was 5:5, and the total thickness of the electrode active material layers was 150 μm.

[0104] (2) Battery manufacturing A polyethylene porous film (10 μm) was prepared as a separator, and the cathode / separator / lithium metal were placed in a coin cell in this order, and an electrolyte was injected to manufacture a battery. The electrolyte was prepared by mixing ethylene carbonate, propylene carbonate, ethyl propionate, and propyl propionate in a mass ratio of 2:1:2.5:4.5, and adding LiPF6 at a concentration of 1.4M.

[0105] Comparative Example 1 Cathode active material (LiNi 0.89 Co 0.07 Mn 0.04 Al 0.01 A slurry (solid content 70wt%) for forming the positive electrode active material layer was prepared by adding 97.11:1.0:0.72:1.17 weight ratios of 1000g / cm2 (Li6CoO2), binder (PVDF), conductive material (acetylene black) and sacrificial positive electrode material (Li6CoO2) to NMP. This was applied to an aluminum thin film (thickness about 10μm) and dried at 60℃ for 6 hours to prepare the positive electrode.

[0106] Next, a negative electrode was prepared in the same manner as in Example 1, and a battery was produced using the negative electrode and positive electrode in the same manner as in Example 1.

[0107] Capacity retention rate evaluation The batteries of Example 1 and Comparative Example 1 were each maintained in an environment of 10% relative humidity for 4 weeks, and the charge / discharge characteristics and capacity retention were evaluated every week. The charge was performed by CC / CV method at 0.2C to 4.25V, with a cut-off of 50mA, and discharged at 0.2C to 2.5V, and the charge / discharge was repeated under the above conditions. This experiment was performed at room temperature (25°C). Figures 1 and 2 are graphs showing the charge capacity and discharge capacity of Example 1, respectively, and Figures 3 and 4 are graphs showing the charge capacity and discharge capacity of the battery of Comparative Example 1, respectively, which were measured immediately after the manufacture of each battery and while maintaining it for one to four weeks. In reference to this, in the case of the battery of Example 1, it was confirmed that the sacrificial positive electrode material was disposed under the electrode active material layer to prevent contact with moisture, and therefore the deterioration of the positive electrode was delayed and the capacity change during charging and discharging was small.

[0108] Meanwhile, the following Table 1 shows the results of measuring the degree of change in moisture content and Li2CO3 content in the positive electrode active material layer while maintaining the positive electrodes obtained in Example 1 and Comparative Example 1 under a relative humidity of 10% for four weeks. It was confirmed that the positive electrode prepared in Example 1 had a smaller moisture content and Li2CO3 content, as well as a smaller increase over time, compared to the positive electrode prepared in Comparative Example 1.

[0109] [Table 1]

[0110] Example 2-1 (1) Preparation of the positive electrode Cathode active material (LiNi 0.89 Co 0.01 Mn 0.1The slurry (solid content 70wt%) for forming the positive electrode active material layer was prepared by adding the positive electrode active material (LiNiO2), binder (PVDF), conductive material (acetylene black) and sacrificial positive electrode material (Li6CoO2) to NMP in a weight ratio of 97.00:1.12:0.60:1.28. The slurry was applied to an aluminum thin film (thickness about 10μm) and dried at 60℃ for 6 hours to prepare the lower layer of the positive electrode active material layer. Next, the positive electrode active material (LiNi 0.89 Co 0.01 Mn 0.1 O2), binder (PVDF) and conductive material (acetylene black) were added to NMP in a weight ratio of 98.74:0.66:0.6 to prepare a slurry (solid content 70 wt%) for forming the upper positive electrode active material layer. The slurry was applied to the surface of the lower layer and dried at 60°C for 6 hours to form the upper layer of the positive electrode active material layer.

[0111] (2) Preparation of the negative electrode A negative active material, binder (PVDF), conductive material (single-walled CNT, LG Chem), and thickener (carboxymethyl cellulose; CMC) were added to NMP in a weight ratio of 97.78:1.15:0.12:0.95 to prepare a slurry (solid content 45 wt%) for forming a negative active material layer. The negative active material was artificial graphite (D50 about 15 μm, specific surface area about 0.9 m 2 / g) and Si (D50 6μm, specific surface area approx. 6m 2 / g) was mixed at a weight ratio of 90:10. It was applied to a copper thin film (thickness about 10 μm) and dried at 60°C for 6 hours to prepare a negative electrode.

[0112] (3) Battery manufacturing A porous polyethylene film (10μm) was prepared as a separator, and the positive electrode / separator / negative electrode were laminated in this order and pressed at 80°C to obtain an electrode assembly. The electrode assembly was placed in a 18650-sized cylindrical metal can (0.2C capacity, 3.0Ah specification) and electrolyte was injected to manufacture a battery. The electrolyte was prepared by mixing ethylene carbonate, propylene carbonate, ethyl propionate, and propyl propionate in a mass ratio of 2:1:2.5:4.5 and adding LiPF6 at a concentration of 1.4M.

[0113] Example 2-2 Li6Co was used instead of Li6CoO2 as the sacrificial cathode material under the cathode active material. 0.7 Zinc 0.3 A battery was manufactured in the same manner as in Example 2-1, except that O4 was used.

[0114] Comparative Example 2 (1) Preparation of the positive electrode Cathode active material (LiNi 0.89 Co 0.01 Mn 0.1 The slurry (solid content 70 wt%) for forming the positive electrode active material layer was prepared by adding the positive electrode active material (Li2NiO2), binder (PVDF), conductive material (acetylene black) and sacrificial positive electrode material (Li2NiO2) to NMP in a weight ratio of 94.28:1.12:0.6:4.0. The slurry was applied to an aluminum thin film (thickness about 10 μm) and dried at 60 °C for 6 hours to prepare the lower layer of the positive electrode active material layer. Next, the positive electrode active material (LiNi 0.89 Co 0.01 Mn 0.1 O2), binder (PVDF) and conductive material (acetylene black) were added to NMP in a weight ratio of 98.74:0.66:0.6 to prepare a slurry (solid content 70 wt%) for forming the upper positive electrode active material layer. This was applied to the surface of the lower layer and dried at 60°C for 6 hours to form the upper layer of the positive electrode active material layer.

[0115] (2) Preparation of the negative electrode The negative active material, binder (PVDF), conductive material (multi-layered CNT, LG Chem), and thickener (carboxymethyl cellulose; CMC) were added to NMP in a weight ratio of 97.4:1.15:0.5:0.95 to prepare a slurry (solid content 45 wt%) for forming the negative active material layer. The negative active material was artificial graphite (D50 about 15 μm, specific surface area about 0.9 m 2 / g) and Si (D50 6μm, specific surface area approx. 6m 2 / g) were mixed in a weight ratio of 90:10. The mixture was applied to a copper thin film (thickness: about 10 μm) and dried at 60°C for 6 hours to prepare a negative electrode.

[0116] (3) Battery manufacturing A battery was produced in the same manner as in Example 2-1.

[0117] Comparative Example 3 (1) Preparation of the positive electrode A positive electrode was prepared in the same manner as in Comparative Example 2.

[0118] (2) Preparation of the negative electrode A negative electrode active material, a binder (PVDF), a conductive material (single-walled CNT, LG Chem), and a thickener (carboxymethyl cellulose; CMC) were added to NMP in a weight ratio of 97.78:1.15:0.12:0.95 to prepare a slurry (solid content 45 wt%) for forming a negative electrode active material layer. The negative electrode active material was artificial graphite (D50 about 15 μm to 16 μm, specific surface area about 0.9 m 2 / g) and Si (D50 6μm, specific surface area approx. 6m 2 / g) were mixed in a weight ratio of 90:10. The mixture was applied to a copper thin film (thickness: about 10 μm) and dried at 60°C for 6 hours to prepare a negative electrode.

[0119] (3) Battery manufacturing A battery was produced in the same manner as in Example 1.

[0120] Example 3 (1) Preparation of the positive electrode A positive electrode active material, a binder (polyvinylidene fluoride; PVDF), a conductive material (acetylene black), and a sacrificial positive electrode material (LiCo6O2) were added to NMP in a weight ratio of 97.00:1.12:0.6:1.28 to prepare a slurry (solid content 70 wt%) for forming a positive electrode active material layer. The slurry was applied to an aluminum thin film (thickness about 10 μm) and dried at 60 ° C for 6 hours to prepare a lower layer of a positive electrode active material layer. Next, a positive electrode active material, a binder (PVDF), and a conductive material (acetylene black) were added to NMP in a weight ratio of 98.74:0.66:0.6 to prepare a slurry (solid content 70 wt%) for forming an upper positive electrode active material layer. The slurry was applied to the surface of the lower layer and dried at 60 ° C for 6 hours to form an upper layer of a positive electrode active material layer.

[0121] The positive electrode active material is LiNi 0.89 Co 0.01 Mn 0.1 O2 and Li2NiO2 are mixed in a weight ratio of approximately 95:5.

[0122] (2) Preparation of the negative electrode A negative electrode active material, binder (PVDF), conductive material (single-walled CNT, LG Chem), and thickener (carboxymethyl cellulose; CMC) were added to NMP in a weight ratio of 97.78:1.15:0.12:0.95 to prepare a slurry (solid content 70 wt%) for forming a negative electrode active material layer. The slurry was applied to a copper thin film (thickness about 10 μm) and dried at 60° C. for 6 hours to prepare a negative electrode. The negative electrode active material was artificial graphite (D50 15-16 μm, specific surface area about 0.9 m 2 / g) and Si (D50 6 μm) were mixed in a weight ratio of 84:16.

[0123] (3) Battery manufacturing A porous film (10μm) made of polyethylene was prepared as a separator, and the positive electrode / separator / negative electrode were laminated in this order and pressed at 80°C to obtain an electrode assembly. The electrode assembly was placed in a 21700-size cylindrical metal can (0.2C capacity, 5.0Ah specification) and electrolyte was injected to manufacture a battery. The electrolyte was prepared by mixing ethylene carbonate, propylene carbonate, ethyl propionate, and propyl propionate in a mass ratio of 2:1:2.5:4.5 and adding LiPF6 at a concentration of 1.4M.

[0124] Comparative Example 4 (1) Preparation of the positive electrode A positive electrode active material, a binder (polyvinylidene fluoride; PVDF), and a conductive material (acetylene black) were added to NMP in a weight ratio of 98.28:1.12:0.6 to prepare a slurry (solid content 70 wt%) for forming a positive electrode active material layer. This was applied to an aluminum thin film (thickness about 10 μm) and dried at 60° C. for 6 hours to prepare a lower layer of a positive electrode active material layer. The positive electrode active material was LiNi 0.89 Co 0.01 Mn 0.1O2 and Li2NiO2 are mixed in a weight ratio of about 95:5. Next, the positive electrode active material (LiNi 0.89 Co 0.01 Mn 0.1 O2), binder (PVDF) and conductive material (acetylene black) were added to NMP in a weight ratio of 98.74:0.66:0.6 to prepare a slurry (solid content 70 wt%) for forming the upper positive electrode active material layer. The slurry was applied to the surface of the lower layer and dried at 60°C for 6 hours to form the upper layer of the positive electrode active material layer.

[0125] (2) Preparation of the negative electrode A negative electrode active material, binder (PVDF), conductive material (single-walled CNT, LG Chem), and thickener (carboxymethyl cellulose; CMC) were added to NMP in a weight ratio of 97.78:1.15:0.12:0.95 to prepare a slurry (solid content 70 wt%) for forming a negative electrode active material layer. The slurry was applied to a copper thin film (thickness about 10 μm) and dried at 60° C. for 6 hours to prepare a negative electrode. The negative electrode active material was artificial graphite (D50 15-16 μm, specific surface area about 0.9 m 2 / g) and Si (D50 6 μm) were mixed in a weight ratio of 90:10.

[0126] (3) Battery manufacturing A battery was produced in the same manner as in Example 2.

[0127] Comparative Example 5 (1) Preparation of the positive electrode A positive electrode active material, a binder (polyvinylidene fluoride; PVDF), and a conductive material (acetylene black) were added to NMP in a weight ratio of 98.28:1.12:0.6 to prepare a slurry (solid content 70 wt%) for forming a positive electrode active material layer. The slurry was applied to an aluminum thin film (thickness about 10 μm) and dried at 60° C. for 6 hours to prepare a lower layer of a positive electrode active material layer. The positive electrode active material was LiNi 0.89 Co 0.01 Mn 0.1 O2 and Li2NiO2 are mixed in a weight ratio of about 95:5. Next, the positive electrode active material (LiNi 0.89 Co 0.01 Mn 0.1O2), binder (polyvinylidene fluoride; PVDF) and conductive material (acetylene black) were added to NMP in a weight ratio of 98.28:1.12:0.6 to prepare a slurry (solid content 70 wt%) for forming a positive electrode active material layer. The slurry was applied to the surface of the lower layer and dried at 60°C for 6 hours to prepare an upper layer of the positive electrode active material layer.

[0128] (2) Preparation of the negative electrode A negative electrode active material, binder (PVDF), conductive material (multi-wall CNT, LG Chem), and thickener (carboxymethyl cellulose; CMC) were added to NMP in a weight ratio of 97.78:1.15:0.12:0.95 to prepare a slurry (solid content 70 wt%) for forming a negative electrode active material layer. The slurry was applied to a copper thin film (thickness about 10 μm) and dried at 60° C. for 6 hours to prepare a negative electrode. The negative electrode active material was artificial graphite (D50 15-16 μm, specific surface area about 0.9 m 2 / g) and Si (D50 6 μm) were mixed in a weight ratio of 90:10.

[0129] (3) Battery manufacturing A battery was produced in the same manner as in Example 2.

[0130] Capacity retention rate evaluation (1) Experiment 1 The capacity retention rate was evaluated by charging and discharging each of the batteries of Example 2-1, Example 2-2, Comparative Example 2, and Comparative Example 3. The charging was performed in a CC / CV mode at 3A until the battery voltage reached 4.2V, and the cut-off voltage was set to 50mA, followed by discharging at 10A until the battery voltage reached 2.5V. The charging and discharging were repeated under these conditions. The experiment was performed at room temperature (25°C). The results are shown in FIG. 7 below. It was confirmed that the battery of Example 2-1 (dash line) had a superior capacity retention rate compared to the batteries of Comparative Example 2 (solid line) and Comparative Example 3 (dashed line). Meanwhile, referring to FIG. 8, it was confirmed that the capacity retention rate of Example 2-2 (dashed line) was at the same level as that of Example 2-1 (solid line).

[0131] (2) Experiment 2 The batteries of Example 3, Comparative Example 4, and Comparative Example 5 were charged and discharged to evaluate the capacity retention rate. The charging was performed by CC / CV method at 3A until the battery voltage reached 4.2V, and the cutoff voltage was set to 50mA, and the battery was discharged at 10A, 20A, and 30A until the battery voltage reached 2.5V. The charging and discharging were repeated under these conditions. The experiment was performed at room temperature. The results are shown in Figs. 9 to 11 below. Fig. 9 shows the results of the battery discharged at 10A. Fig. 10 shows the results of the battery discharged at 20A. Fig. 11 shows the results of the battery discharged at 30A. As can be seen from Figs. 9 to 11, it was confirmed that the battery of Example 3 had a superior capacity retention rate to Comparative Examples 4 and 5. Here, in each of Figs. 9 to 11, the chain line indicates Example 3, the dashed line indicates Comparative Example 4, and the solid line indicates Comparative Example 5.

Claims

1. A positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, the positive electrode active material layer includes a lower layer disposed on a surface of a current collector and an upper layer disposed on an upper surface of the lower layer, the upper layer includes a first positive electrode active material, a conductive material, and a binder resin; the lower layer includes a second positive electrode active material, a sacrificial positive electrode material, a conductive material, and a binder resin; The first and second positive electrode active materials each independently include at least one selected from the group consisting of compounds represented by Formula 1: [Chemical formula 1] Li++ 1-x M x O 2 In the formula 1, M includes at least one of Mn, Co, Al, Cu, Fe, Mg, B, and Ga; x is 0 to 0.5; The upper layer does not include a sacrificial cathode material; The sacrificial cathode material in the lower layer includes at least one of Li 6 CoO 4 and a compound represented by the following Formula 2: [Chemical formula 2] Li 6 Co 1-x Zn x O 4 In the above Chemical Formula 2, x is 0 or more and 1 or less.

2. The sacrificial positive electrode material is Li 6 CoO 4 and Li 6 Co 0.7 Zinc 0.3 O 4 The positive electrode for a secondary battery according to claim 1 , comprising at least one selected from the following:

3. 2. The positive electrode for a secondary battery according to claim 1, wherein the sacrificial positive electrode material is contained in a range of 1 wt % to 20 wt % with respect to 100 wt % of the lower layer.

4. 2. The positive electrode for a secondary battery according to claim 1, wherein the sacrificial positive electrode material is contained in an amount of 10 wt% or less relative to 100 wt% of the entire positive electrode active material layer.

5. 2. The positive electrode for a secondary battery according to claim 1, wherein in Chemical Formula 1, x is 0 or more and 0.15 or less.

6. The positive electrode for a secondary battery according to claim 1 , wherein in Formula 1, M comprises two or more of Co, Al, and Mn.

7. The formula 1 is LiNi 1-x (Co, Mn, Al) x O 2 2. The positive electrode for a secondary battery according to claim 1, wherein the Al is contained in an atomic ratio of 0.001 to 0.02 relative to Ni.

8. A lithium ion secondary battery comprising a positive electrode, a negative electrode, an insulating separator interposed between the positive electrode and the negative electrode, and an electrolyte solution, The positive electrode is a positive electrode for a secondary battery according to claim 1 , The negative electrode includes a silicon-based compound as a negative electrode active material and a linear conductive material as a negative electrode conductive material, The conductive material includes a linear conductive material.

9. The silicon-based compound includes at least one compound represented by the following formula 3: [Chemical formula 3] Yes x The secondary battery according to claim 8 , wherein in Chemical Formula 3, x is 0 or more and less than 2.

10. The secondary battery of claim 9 , wherein x in Chemical Formula 3 is 0.5 or more and 1.5 or less.

11. The secondary battery according to claim 8 , wherein the linear conductive material comprises at least one selected from the group consisting of single-walled carbon nanotubes, multi-walled carbon nanotubes, and graphene.

12. The secondary battery according to claim 8 , wherein the linear conductive material comprises a single-walled carbon nanotube.

Citation Information

Patent Citations

  • Anode active material, method for preparing same, and device using anode active material

    CN109980199A

  • Negative electrode plate for lithium secondary battery and lithium secondary battery including the same

    JP2018503234A

  • Positive electrode and non-aqueous electrolyte secondary battery

    JP2019140054A

  • Method of manufacturing composite particles

    JP2020053315A

  • Manufacturing method of lithium ion secondary battery

    JP2020102347A